Honey bee Apis mellifera L. responses to oxidative stress induced by pharmacological and pesticidal compounds - Tahir, Faizan; Goblirsch, Michael; Adamczyk, John; Karim, Shahid; Alburaki, Mohamed (Frontiers in Bee Science, 2023)
The western honey bee, Apis mellifera L., is a eusocial insect that plays a significant role in ecosystem balances and pollination of plants and food crops. Honey bees face multiple biotic and abiotic stressors, such as pathogens, diseases, chemical pesticides, and climate change, which all contribute to honey bee colony loss. This study investigated the impacts of multiple pharmacological and pesticide molecules on honey bee survival and gene regulation responses. In an 11-day cage experiment, sublethal doses of tunicamycin, thapsigargin, metformin, paraquat, hydrogen peroxide, and imidacloprid were administered to newly emerged sister bees. Daily treatment consumption and mortality were recorded, as well as the transcription expression of twelve major genes (AChE-2, Apisimin, Apidaecin, mrjp1, Sodq, cp450, SelT, SelK, Ire1, Xbp1, Hsc70), some of which are markers of oxidative and endoplasmic reticulum (ER) stresses in honey bees. At day 9 of the treatments, protein damage was quantified in caged bees. Kaplan-Meier model indicated significant (p < 0.001) toxicological effects of paraquat, H2O2, and tunicamycin on bee survivorship compared to controls with better survivals for other molecules.Post-ingestive aversion responses were recorded only for of tunicamycin, hydrogen peroxide, and imidacloprid. Nonetheless, significantly higher protein damage on day 9 was only identified in bees exposed to paraquat and imidacloprid. Some antioxidant genes significantly regulated vis-àvis specific treatments. Our results reveal age-related regulation of other major genes with significant inter-gene positive correlations.